2002
DOI: 10.1046/j.1440-1754.2002.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood invasive pneumococcal disease in Tasmania, 1994−2000

Abstract: The incidence of invasive pneumococcal disease was comparable to many urban populations in Australia. The high rate of predisposing conditions supports the recommendations of the Australian Technical Advisory Group on Immunisation for targeted immunization in this group. The paucity of data describing Indigenous status is an argument for improved data collection in this area. The low level of penicillin resistance necessitates ongoing surveillance, and the lack of serotype information requires prospective data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
4
2
0
Order By: Relevance
“…The most common type of IPD in this study population was pneumonia, similar to observation from Greece 12 . However, studies from Canada, 1 Tasmania 11 and Sydney 13 showed that BWF was the most common type of IPD. These differences persisted even if the probable cases of pneumococcal pneumonia were excluded from the present study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The most common type of IPD in this study population was pneumonia, similar to observation from Greece 12 . However, studies from Canada, 1 Tasmania 11 and Sydney 13 showed that BWF was the most common type of IPD. These differences persisted even if the probable cases of pneumococcal pneumonia were excluded from the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Observations from this hospital‐based study are very similar to reports from Costa Rica and Tasmania 2,11 . IPD is predominantly a disease of young children, affecting mainly children younger than 5 years of age.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Age distribution, disease types, predisposing conditions and complications are similar to figures reported in other studies [20,21]. There were several complications related to IPD, which required surgical intervention.…”
Section: Discussionsupporting
confidence: 83%